2002
DOI: 10.1039/b2rp90014a
|View full text |Cite
|
Sign up to set email alerts
|

Mental Models in Chemistry: Senior Chemistry Students’ Mental Models of Chemical Bonding

Abstract: ABSTRACT:In this paper we describe research into learners' mental models for chemical bonding. New Zealand senior secondary students, undergraduates and postgraduates' mental models for chemical bonding were probed using an interview protocol that included the use of a variety of common substances and focus cards that depicted model use in some way. The study found that the learners' mental models were simple and realist in nature, in contrast with the sophisticated and mathematically complex models they were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 33 publications
4
48
0
10
Order By: Relevance
“…In Tables 1-3 we provide data for changes in student ideas concerning the uncertainty principle, the nature of orbitals and the atomic model. Employing a chi-squared statistical test, changes for the last two concepts were found to be statistically significant (Tables 1, 2 Research has shown that students at all levels prefer concrete or simple abstract models, for example: space-filling models of atoms and molecules (Harrison & Treagust, 1996); the Bohr model of the atom (Fishler & Lichtfeldt, 1992;Nicoll, 2001;Petri & Niedderer, 1998); or the octet rule (Coll & Taylor, 2002). These preliminary models are very stable.…”
Section: Changes In Students' Ideasmentioning
confidence: 99%
“…In Tables 1-3 we provide data for changes in student ideas concerning the uncertainty principle, the nature of orbitals and the atomic model. Employing a chi-squared statistical test, changes for the last two concepts were found to be statistically significant (Tables 1, 2 Research has shown that students at all levels prefer concrete or simple abstract models, for example: space-filling models of atoms and molecules (Harrison & Treagust, 1996); the Bohr model of the atom (Fishler & Lichtfeldt, 1992;Nicoll, 2001;Petri & Niedderer, 1998); or the octet rule (Coll & Taylor, 2002). These preliminary models are very stable.…”
Section: Changes In Students' Ideasmentioning
confidence: 99%
“…These latter authors have reported on the mental models for chemical bonding used by secondary, undergraduate, and postgraduate students from Australia and New Zealand (Coll & Taylor, 2002). They found that the "sea of electrons" model was a preferred model at all three levels.…”
Section: Learners' Ideas About Metallic Structure and Bondingmentioning
confidence: 99%
“…As a result, teachers find it challenging to provide explanations that assist students in developing a deep understanding of the molecular-level processes that are occurring. Much research has been conducted into the reasons for the difficulties experienced by chemistry students in learning about such concepts (e.g., Coll & Taylor, 2002;Gabel, 1999;Johnstone, 2000;Treagust, Duit, & Nieswandt, 2000). The central finding of this research is that students experience difficulties for two main reasons.…”
Section: Case Study 2 Using Multimedia To Support Students' Learningmentioning
confidence: 99%
“…The results of the test were used to design and sequence learning experiences that would place emphasis on and scaffold students' learning in appropriate areas. The sequencing and teaching strategies were also informed by research about ways to minimise the development of misconceptions in chemistry students (e.g., Coll & Taylor, 2002;Tan & Treagust, 1999). Strategies focused on developing students' understanding of key concepts through the use of multiple visual and symbolic representations.…”
Section: Teaching Strategiesmentioning
confidence: 99%